Beaufort Sea planning area : oil and gas lease sale 124 : draft environmental impact statement. - United States. Minerals Management Service. Alaska OCS Region. ([Anchorage, Alaska?] : U.S. Dept. of the Interior, Minerals Management Service, Alaska OCS Region, 1990)
"MMS 90-0006." "OCS EIS/EA." "February 1990." At head of title: Alaska Outer Continental Shelf. Includes bibliographical references (vol. I, p. 1-30) and index. Mode of access: Internet.